2022
DOI: 10.1021/acsenergylett.2c01444
|View full text |Cite
|
Sign up to set email alerts
|

Gas Generation in Lithium Cells with High-Nickel Cathodes and Localized High-Concentration Electrolytes

Abstract: High-nickel layered-oxide cathodes (LiNi x Mn y Co 1-x-y O 2 , x ≥ 0.8) exhibit high capacities but also experience rapid capacity fade during cycling, and are susceptible to heat generation and gas release. Advanced electrolytes, such as localized high-concentration electrolytes (LHCEs), substantially stabilize the cathode during cycling and have lower flammability than conventional electrolytes, but gas generation with these electrolytes is yet to be assessed. We demonstrate here that gas generation from a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…Severe gas evolution (CO 2 , O 2 , CO, etc.) at 4.6 V was reported in 1,2-dimethoxyethane (DME)-based LHCEs due to solvent oxidation . Under high-rate charging conditions, the uneven Li deposition tends to induce dendrite growth and increase polarization, accelerating active Li consumption and even short-circuiting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe gas evolution (CO 2 , O 2 , CO, etc.) at 4.6 V was reported in 1,2-dimethoxyethane (DME)-based LHCEs due to solvent oxidation . Under high-rate charging conditions, the uneven Li deposition tends to induce dendrite growth and increase polarization, accelerating active Li consumption and even short-circuiting .…”
Section: Introductionmentioning
confidence: 99%
“…at 4.6 V was reported in 1,2-dimethoxyethane (DME)-based LHCEs due to solvent oxidation. 25 Under high-rate charging conditions, the uneven Li deposition tends to induce dendrite growth and increase polarization, accelerating active Li consumption and even short-circuiting. 26 These results point out that the interphase composition and structure established by the anion chemistry have shown inadequacy for protecting ultrahigh-voltage cathodes and reactive Li-metal anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shielding effect of diluent molecules, the Li + –anion interactions could be intensified in the inner solvation sheath, which further improves the cycling stability of high-voltage LMBs. In addition, weakly solvating ether solvents with steric groups or electron-withdrawing groups were proposed to further increase the enrichment of anions in the solvation complex and promote the anion-related interfacial reactions. However, the reliance on anion-related interfacial reactions for cathode protection has fallen short of further expanding the anodic stability of ether-based electrolytes beyond 4.5 V . Because of the ever-increasing need for ultrahigh-voltage cathodes, it is critical to seek effective design strategies to further improve the oxidation stability of ether-based electrolytes for LMB applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent developments of localized high concentration electrolytes with non-solvating diluents (e.g., hydrofluoroethers) not only improve the physical properties of the electrolytes (e.g., viscosity, ionic conductivity, wettability, etc.) but also enhance the electrochemical stability of ether electrolytes [18][19][20][21][22][23] . However, recent studies have found the instability of DME-based electrolytes under higher voltages over 4.5 V 18 .…”
mentioning
confidence: 99%
“…but also enhance the electrochemical stability of ether electrolytes [18][19][20][21][22][23] . However, recent studies have found the instability of DME-based electrolytes under higher voltages over 4.5 V 18 . For future applications of ether electrolytes, it is urgent to further improve the electrolyte oxidation stability on Ni-rich cathodes with reactive Ni 3+ /Ni 4+ surface sites.…”
mentioning
confidence: 99%